2007
DOI: 10.1016/j.molcel.2006.11.008
|View full text |Cite
|
Sign up to set email alerts
|

M Domains Couple the ClpB Threading Motor with the DnaK Chaperone Activity

Abstract: The AAA(+) chaperone ClpB mediates the reactivation of aggregated proteins in cooperation with the DnaK chaperone system. ClpB consists of two AAA domains that drive the ATP-dependent threading of substrates through a central translocation channel. Its unique middle (M) domain forms a coiled-coil structure that laterally protrudes from the ClpB ring and is essential for aggregate solubilization. Here, we demonstrate that the conserved helix 3 of the M domain is specifically required for the DnaK-dependent shuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
193
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(213 citation statements)
references
References 34 publications
15
193
2
1
Order By: Relevance
“…The potential crowbar function is also unnecessary to disaggregate aggregated GFP, another reaction that both chaperones can separately carry out. The possibility that the middle domain may mediate communication between NBD-1 and NBD-2 (20) or between ClpB and DnaK seems more plausible (21). Regardless of the precise mechanism, our results show that the two systems work synergistically in protein disaggregation, with the DnaK system very likely acting concomitantly with ClpB.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The potential crowbar function is also unnecessary to disaggregate aggregated GFP, another reaction that both chaperones can separately carry out. The possibility that the middle domain may mediate communication between NBD-1 and NBD-2 (20) or between ClpB and DnaK seems more plausible (21). Regardless of the precise mechanism, our results show that the two systems work synergistically in protein disaggregation, with the DnaK system very likely acting concomitantly with ClpB.…”
Section: Discussionmentioning
confidence: 65%
“…1B). Experiments have implicated the middle domain in coordinating the communication between NBD-1 and NBD-2 (20) as well as the interaction of ClpB with the DnaK system (11,21).…”
mentioning
confidence: 99%
“…Although the physical nature of this interaction remains unknown, an ATP-driven M-domain motion has been demonstrated previously for ClpB (35,47). It is tempting to speculate that Hsp70 binding to the M-domain stabilizes or alters an M-domain conformation from a normally inactive to an active state.…”
Section: Discussionmentioning
confidence: 78%
“…The Hsp104 M-domain coiled-coil is composed of four α-helices, which can be subdivided into two smaller coiled-coils, termed motif 1 and motif 2 (5,6). It was previously shown that mutations in the ClpB M-domain helix 2 had a small but significant effect on substrate recovery (34), whereas mutations in helix 3 abrogated protein disaggregation (35), which was attributed to a potentially impaired interaction between ClpB and DnaK (35).…”
Section: Resultsmentioning
confidence: 99%
“…Catalytic Turnover Triggers Subunit Exchange-Dissociation of the proteins making up the ring structure has been suggested as a possible mechanism of AAAϩ proteins releasing their product after catalysis (28). Magnesium chelatase is unusual in the sense that Mg-protoporphyrin IX rather than a protein is the ultimate product of the AAAϩ activity, although the BchH subunit is the target of the BchID complex.…”
Section: Mutant-derived Bchi and Wild-type Bchd Form A Complex-r Capmentioning
confidence: 99%